Design, development and preliminary evaluation of a new wearable vital signs monitor for cattle - Quispe Bonilla, Max (2019)
The monitoring of various vital signs in cattle is important from the point of view of production, health and animal welfare; however, there are few devices that have the potential to be used at the field level and that are not invasive. For this reason, the present work was carried out with the purpose of designing, constructing and evaluating the use of wearable vital signs monitor (MOSIVILLe), which is capable of capturing the vital signs in cattle under field conditions. The design and development of MOSIVILLe was carried out in Lima, Peru, between January and October 2017 and the field evaluation was carried out in Chota, Peru, using 11 heifers between November 2017 and February 2018. The vital signs of cattle were obtained with the MOSIVILLe, recognizing the P, Q, R, S, T waves, QRS complex and RR interval of the electrocardiogram that led to obtain the heart rate (HR). Additionally, the skin temperature (T°S) and the ventilation signal were obtained with the peaks of inhalation, exhalation, inspiration time and expiration time that determine the respiratory frequency (RF). MOSIVILLe used in cattle in field conditions allowed to obtain an HR of 70.83±1.47, RF of 25.24±1.64 and a T°S of 31.52±0.40 (mean ± standard error), values that agree with the literature. It is concluded that MOSIVILLe is an important alternative to obtain various vital signs in cattle under field conditions.